2015
DOI: 10.1007/s11930-015-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Advocating For a Transdisciplinary Perspective in Sexual Medicine

Abstract: Editor-in-Chief commentary on the 2014 re-launch of Current Sexual Health Reports. CommentaryThe first year of the re-launched Current Sexual Health Reports was successfully completed with 30 articles being carefully reviewed and shepherded to publication by our editorial board and section editors. They are deserving of our thanks and appreciation for their hard work, and we offer special thanks to our authors for their fine contributions. As we enter 2015, I also want to share a bit of personal history, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A safe effective medication for DE does not yet exist. When and if such a drug becomes available, this author’s transdisciplinary perspective supports the appropriate use of that medication when combined with counseling ( 6 ). However, there are still numerous techniques, which can be combined to treat DE including and not limited to sex education, cognitive-behavioral therapy, mindfulness, psychodynamic exploration of underlying conflicts, and/or couples therapy ( 56 , 57 ).…”
Section: Psychosexual Therapy Of De Based On the Stp Modelmentioning
confidence: 99%
“…A safe effective medication for DE does not yet exist. When and if such a drug becomes available, this author’s transdisciplinary perspective supports the appropriate use of that medication when combined with counseling ( 6 ). However, there are still numerous techniques, which can be combined to treat DE including and not limited to sex education, cognitive-behavioral therapy, mindfulness, psychodynamic exploration of underlying conflicts, and/or couples therapy ( 56 , 57 ).…”
Section: Psychosexual Therapy Of De Based On the Stp Modelmentioning
confidence: 99%
“…The biopsychosocial model of sexual health management is often considered the gold standard because it emphasizes that sexual dysfunctions involve a complex interplay of biological, psychological, interpersonal, and sociocultural factors. 1 , 2 , 3 This model is the foundation for clinical theories and paradigms including the sexual tipping point, 4 the dual-control model, 5 and systemic sex therapy. 6 …”
Section: Introductionmentioning
confidence: 99%
“…This multi-disciplinary model is not unique to sexual health care delivery, as it has been shown to be effective in other health care settings, including primary care, obesity management, and cancer survivorship. 3 , 7 Specifically within the field of sexual health, a number of studies have shown promising results using this multi-disciplinary framework to successfully treat various sexual health concerns, particularly female sexual dysfunction. 8 , 9 , 10 , 11 , 12 , 13 Despite promising clinical outcomes of multi-disciplinary treatment for sexual health, much is unknown about this model.…”
Section: Introductionmentioning
confidence: 99%
“…The BPS requires multidisciplinary cooperation, eclecticism and flexibility, elements that still cannot be taken for granted in any social or health care context. Most of the time, medical and non-medical health care providers work separately, making it difficult to establish cross-collaboration for both clinical and research purposes (Perelman, 2015). It is essential for different specialists to work together to share aims and treatment algorithms and recognize the specificity of each professional figure (Kirana et al, 2013;Reisman et al, 2015).…”
Section: Some Shadows Of the Bps Model: When Culture And Attitudes Are Neglectedmentioning
confidence: 99%